BALAI PENDIDIKAN DAN PELATIHAN BADAN NASIONAL PENCARIAN DAN PERTOLONGAN DI KABUPATEN KUBU RAYA - Walidain, Muhammad Ananda; Purnomo, Yudi; Pebriano, Valentinus (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2024)
The National Search and Rescue Agency (Badan Nasional Pencarian dan Pertolongan or BNPP) is an institution responsible for conducting search and rescue operations related to disasters in a particular area. This institution is also obligated to prepare human resources who are experts in the field of search and rescue. The quality of its human resources is built through regular training. This requires a facility or container that meets the standard educational and training needs of BNPP personnel. This design aims to produce a design for the Education and Training Center of the National Search and Rescue Agency in Kubu Raya Regency. Thus, the quality of BNPP personnel, especially in the Kalimantan region, can be maintained. The design method used is the Richard Whitaker design method. This method includes stages, starting from the introduction of the BNPP institution, collecting planning issues for the BNPP Education and Training Center, collecting theories related to the BNPP Education and Training Center, analyzing design standards, formulating design concepts and solutions to be used, as well as creating and technical drawings. Through this method, a design concept is obtained with a theme of good spatial comfort that can make the function of the BNPP Education and Training Center area more effective. This will then serve as the basis for producing the design of the BNPP Education and Training Center in Kubu Raya Regency.